A review of inherent assessment for sustainable process design - Athar, M. (Elsevier Ltd, 2019)
Chemical process manufacturing is associated with risks, which cannot be eliminated. Anyhow, controlling or minimizing of risks is possible up to a certain extent through various process safety strategies. Among these strategies, the inherent approach offers a sustainable process design. This review aims to offer an extensive survey regarding the bibliometrics and the features of the state-of-the-art inherent assessment methods. For the bibliometric part, numerous trends like publication trend, authors and geographical cooperation and prominent keywords are presented using the VOSviewer software. For the second intention, the scope and features of inherent assessments methods for sustainable process design are discussed in addition to the historical development of these methods. The techniques are categorized among seven groups based on the method adopted for inherent assessment along with the benefits and detriments of each group. It is revealed that initially, the inherent assessment has focused on the comparison of various process routes, whereas, the modern methods intend to minimize the risk. Furthermore, it is recognized that the process equipment approach is not much explored yet, which may improve the sustainable process designing via the equipment characteristics. Finally, the limitations of present schemes and future research directions for inherent assessment implications in the sustainable process design are also highlighted, such that the objectives of economic, healthier, safer and environmental-friendly process plants can be materialized. Â© 2019 Elsevier Ltd